Female Graduate Students on Masculinity: â€œHis girly characteristics worried me and my husbandâ€ - Yumarnamto, Mateus (Widya Mandala Catholic University Surabaya, 2015)
This paper explores the masculinity discourses appearing in an internet discussion forum in a graduate class. The discussion forum itself is a part of a course related to contemporary issues, media, and identity in literature for children and young adults. In the forum the students are required to respond to the weekly readings, especially the ones related to children and young adult literature. This study is aimed at understanding how masculinity discourses are presented by the members of the forum. There are two main thematic discourses found in the discussion forum. The first one is the dominant discourses of masculinity in which boys should be boys by showing their macho sides. The second one is the subordinate discourse of masculinityâ€”the feminine sides of men. Beyond the texts and academic discussions, these findings show that the hegemonic masculinity persists and unconsciously has influenced many members of the forum. Keywords: masculinity, children literature, readersâ€™ response, discussion forum